HIDROGENOLISIS METILSIKLOPENTANA PADA KATALIS 0.3% Pt/Al2O3 - Hery Haerudin (Jurnal Kimia Terapan Indonesia, 1996)
Hydrogenolysis of methylcyciopentane (MCP) was carried out with 0.3% Pt/Al2O3 catalyst at 210 °C and 235 °C in a batch reactor. Chemisorption of hydrogen and oxygen on the catalyst had also been measured. The mean value of platinum dispersion on the catalyst support measured by chemisorption technique was D = 84%. The product distribution of hydrogenolysis of MCP, namely n- hexane : 2- methylpentane : 3-methylpentane was found to be 15: 55: 30 at 210 DCand 20: 50: 30 at 235 °C. The adsorption of MCP molecule at the boundary area between the metal particle and the support material was assumed to be the determining factor for that distribution profile. The activation energy (Ea) of the hydrogenolysis of MCP on this catalyst was 95 kJ/mol.